Gestión de inventarios en las empresas industriales de plásticos - Reyes Rodríguez, Rosanna Bertha (2023)
The investigation entitled Inventory Management in the industrial companies of Plastics develops because the sector presents certain problems such as the shortage of the raw material having to acquire them at greater price, the waste of materials during the production that leads them to lose money. To this is added, the outdated information of the materials and products, the ignorance of the real need for raw material and the lack of a sales forecast to acquire the materials. In view of this, the study aims to determine the impact of inventory management on the productivity of plastic industrial companies. The methodology that is applied lies in a mixed approach, descriptive, documentary and field research, as well as the inductive method, the survey techniques, interview and observation are used, while the sample is 14 industrial companies in Plastic of the city of Guayaquil. The findings showed that despite the fact that a large part of the companies have manuals and policies for the process of receiving, storage and inventory control 71.4%, there is a coordination problem between the purchasing-bodega area 28.6%, they do not have a Budget for Inventory Acquisitions 71.4%, being the management process that generates acquisitive losses 35.7%, finding as more inconvenience the breakage of stock 28.6%. In turn, it is found that inventory management affects the absolute liquidity of the company due to budget reduction, delays in productive processes due to lack of supplies and sales losses 38.5%, which causes them to buy not planned inputs 35.7 %, so they consider that poor management affects productivity 83.3%. It is concluded that inventory management impacts the productivity of plastic industrial companies.